2014
DOI: 10.1101/gad.231233.113
|View full text |Cite
|
Sign up to set email alerts
|

D-2-hydroxyglutarate produced by mutant IDH2 causes cardiomyopathy and neurodegeneration in mice

Abstract: Mutations in isocitrate dehydrogenase 1 and 2 (IDH1/2) have been discovered in several cancer types and cause the neurometabolic syndrome D2-hydroxyglutaric aciduria (D2HGA). The mutant enzymes exhibit neomorphic activity resulting in production of D2-hydroxyglutaric acid (D-2HG). To study the pathophysiological consequences of the accumulation of D-2HG, we generated transgenic mice with conditionally activated IDH2 R140Q and IDH2 R172K alleles. Global induction of mutant IDH2 expression in adults resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 52 publications
2
73
0
1
Order By: Relevance
“…S1C). A previous report indicated that overproduction of D2-HG, caused by a broadly expressed mutant IDH2, is associated with cardiac hypertrophy, dilatation, and failure (8). We found no cardiac hypertrophy in transplanted mice with Idh2…”
Section: Significancesupporting
confidence: 43%
See 2 more Smart Citations
“…S1C). A previous report indicated that overproduction of D2-HG, caused by a broadly expressed mutant IDH2, is associated with cardiac hypertrophy, dilatation, and failure (8). We found no cardiac hypertrophy in transplanted mice with Idh2…”
Section: Significancesupporting
confidence: 43%
“…To understand whether overproduction of D2-HG alone was responsible for the effects observed in the Idh2 mutant mouse model, we measured rates of substrate metabolism in the isolated working rat heart and conducted computational flux rate analysis using the CardioNet model of mammalian cardiac metabolism (14). Rat hearts were perfused ex vivo in the presence or absence of D2-HG in concentrations similar to those found in the plasma of Idh2 R140Q mutant mice (0.5 mM) and AML patients (8,(15)(16)(17) and those reported by Latini et al (18) to promote inhibition of ATP synthase in cardiac muscle in vitro (range 0.05-5 mM; F 0 /F 1 ATP synthase K i = 0.47 ± 0.18 mM) (Fig. 1A).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed using anti-CD138, anti–Ki-67, and anti–c-Myc, as previously reported (37). …”
Section: Methodsmentioning
confidence: 99%
“…5,14,[18][19][20] Targeting mutant IDH1 or IDH2 to the mouse central nervous system (CNS) results in neurodegeneration or perturbed basement membrane function, without evidence yet that it can drive tumorigenesis in the CNS. 14,21 IDH mutations are being pursued as therapeutic targets. 10,[22][23][24] However, the mechanisms by which IDH mutants contribute to cancer pathogenesis remain only partially understood.…”
Section: Introductionmentioning
confidence: 99%